Frequency of antimicrobial resistance and integron gene cassettes in Escherichia coli isolated from giant pandas (Ailuropoda melanoleuca) in China. (March 2018) - Zou, Wencheng; Li, Caiwu; Yang, Xin; Wang, Yongxiang; Cheng, Guangyang; Zeng, Jinxin; Zhang, Xiuzhong; Chen, Yanpeng; Cai, Run; Huang, Qianru; Feng, Lan; Wang, Hongning; et al.
Abstract: Escherichia coli ( E. coli ) is considered as a common opportunistic pathogen, which causes seriously intestinal infections to giant pandas ( Ailuropoda melanoleuca ) and other animals. The aim of this investigation was to characterize the antimicrobial resistance and integron gene cassettes in E. coli isolated from the faeces of giant pandas in China. A total of 89 E. coli were isolated, after diagnosis of isolates and genomes were extracted. All the isolates were screened for the presence of related drug-resistance genes and integron gene cassettes through the Polymerase Chain Reaction (PCR) and sequencing. In addition, antimicrobial resistance testing was performed according to the standard disk diffusion method (CLSI 2013). The results demonstrated that all the isolates were multi-drug resistance (MDR). High resistance proportions of the E. coli isolates were to streptomycin (93%), cefazolin (90%), amikacin (75%), tetracycline (65%), ampicillin (62%), cefotaxime and trimethoprim-sulfamethoxazole (54%, each). With respect to the various resistance genes; bla CTX-M, sul1, ant (3′)-Ia, tetA, qnrB, tetE, floR, aac (6′)-Ib, sul2, rmtA, cmlA, rmtB and tetC were identified with the respective frequencies of 44%, 45%, 38%, 37%, 35%, 27%, 26%, 20%, 18%, 15%, 10%, 7% and 4%. None of the isolates was positive for qnrA and cfr genes. Moreover, a further investigation of integron revealed that the emergence of class 1 and 2 integrons were in 47% and 8% isolates, respectively. While class 3 integron was not screened. Six types of containing in class 1 integron specific gene cassettes ( dfrA12-orfF-aadA2, dfrA17-aadA5, aadA1, aadA5, dfrA1 and dfrA7 ) were identified. However, only one gene cassette ( dfrA1-sat2-aadA1 ) was detected in class 2 integron. These finding emphasize that a high level of E. coli isolates harbored antibiotics resistance and integron gene cassettes, which may bring so many potential threats to the health of giant pandas. Highlights: This is the first report about integron gene cassettes in E. coli isolated from the faeces of giant pandas in China. High multi-drug resistance rates have been discovered in the E. coli isolated from the faeces of giant pandas in this study. Wide prevalence of antibiotic resistance genes and integron gene cassettes were found in the faeces of giant pandas.